Hemoglobins Likely Function as Peroxidase in Blood Clam Tegillarca granosa Hemocytes - Sufang Wang; Xiaopei Yu; Zhihua Lin; Shunqin Zhang; Liangyi Xue; Qinggang Xue; Yongbo Bao (Journal of Immunology Research)
Hemoglobins are a group of respiratory proteins principally functioning in transport of oxygen and carbon dioxide in red blood cells of all vertebrates and some invertebrates. The blood clam T. granosa is one of the few invertebrates that have hemoglobin-containing red hemocytes. In the present research, the peroxidase activity of T. granosa hemoglobins (Tg-Hbs) was characterized and the associated mechanism of action was deciphered via structural comparison with other known peroxidases. We detected that purified Tg-Hbs catalyzed the oxidation of phenolic compounds in the presence of exogenous H2O2. Tg-Hbs peroxidase activity reached the maximum at pH 5 and 35°C and was inhibited by Fe2+, Cu2+, SDS, urea, and sodium azide. Tg-Hbs shared few similarities in amino acid sequence and overall structural characteristics with known peroxidases. However, the predicted structure at their heme pocket was highly similar to that of horseradish peroxidase (HRP) and myeloperoxidase (MPO). This research represented the first systemic characterization of hemoglobin as a peroxidase.